Análise da relação entre investimentos ambientais e desempenho econômico - Flores, Giovana Shai’anne da Silva (Universidade do Vale do Rio do Sinos, 2009)
This study investigates the relationship between environmental investment and economic performance of firms that published in the social balance through the Brazilian Institute of Social and Economic Analysis (IBASE) in the period between 1996 to 2007. Using archetypes built from a focus group through system dynamics, there was defined the variables used on the regression analyses with panel data. The results indicate that the Internal Environmental Investments (IEI) and the External Environmental Investments (EEI) impact significantly the Liquid Revenue (LR) of the firms and the Operational Result (OR). When the variables defined by the focus group were related to the LR there is no co-relation among the IEI. However, the EEI are highly co-related and the variables Investment on Immobilized and Gross Domestic Product (GDP) also present a positive co-relation with LR. On the use of rates to observe that both IEI and Investment on Immobilized present a negative co-relation with LR, while EEI and GDP present a
Keywords: dados em painel; desempenho econômico; dinâmica de sistemas; grupo de foco; investimento ambiental; economic performance; focus group; panel data; system dynamics; environmental investment; Ciências Sociais Aplicadas